Plant Foods By‐Products as Sources of Health‐Promoting Agents for Animal Production: A Review Focusing on the Tropics. (1st September 2016) - Guil‐Guerrero, J. L.; Ramos, L.; Moreno, C.; Zúñiga‐Paredes, J. C.; Carlosama‐Yepez, M.; Ruales, P.
Abstract : In recent years there has been an increasing trend toward antibiotic use for animal production in tropical countries. As a suitable alternative to such drugs, several highly available plant‐food by‐products are reviewed here as supplements to feed farm animals. Such materials contain bioactive compounds, such as phenolics, carotenoids, saponins, essential oils, active peptides, and sterols. Phenolics are abundant in mango, avocado, and potato peels and are also found in pineapple and papaya by‐products. Phenolic compounds include (i) phenolic acids, which have antibacterial properties and can reduce the potential transmission of bacteria from cattle to the environment; (ii) flavonoids, which can exert antibacterial activity and induce synergy with other antibacterial agents against some resistant strains of bacteria; and (iii) tannins, which have benefits for ruminant productivity and health, although adverse effects have been also reported. Carotenoids enhance immunity in farm animals and are found in high amounts in papaya and tomato by‐products. Saponins occur in cassava by‐products and potato peels. Such compounds improve growth, feed efficiency, and health in ruminants, although there are also reports about their negative effects on farm animals. Recent investigations have shown that essential oils have a high potential as antibiotic growth promotant replacers due to their significant antimicrobial activity. These are abundant in mango peels. This review assesses the occurrence of active compounds in tropical crop by‐products, worldwide production, and the healthy effects of active compounds in farm animals. Crop by‐products from tropical countries contain high levels of bioactive compounds. Mango, avocado, and potato peels contain high concentrations of phenolics. By‐products of tropical origin could help against microbial resistance to antibiotics. Carotenoids stand out in papaya by‐products and essential oils in mango peels.